Faktor lingkungan yang mempengaruhi keberadaan hama yang mengganggu penghuni rumah di Kota Pekanbaru - Sutikno, Agus; Rasyad, Aslim; Amin, Bintal; Mahatma, Radith (Dinamika Lingkungan Indonesia, 2021)
Pests that are often a household problem in several cities in Indonesia are mosquitoes, rats, cockroaches, flies. Causes of settlement pests are dirty environments, food scraps, rubbish, and waterlogged gutters / ditches. The presence of pests in the house causes occupants to control pesticides. Pesticides are used primarily to control mosquitoes, ants, flies, cockroaches, mice and termites. This research is a descriptive research that aims to explain, detail and make a description of a phenomenon or object under study. The target population in this study is households residing in Pekanbaru City, namely in the Districts of Tenayan Raya, Sail and Pekanbaru City with three clean, medium and dirty categories. Determination of the sample is done purposively with multistage sampling technique. The sample was determined purposively with multistage sampling technique and the total sample was 101 households. The data obtained were nominal, ordinal and ratio, analyzed the relationship between these data using chi-square. The results showed that the physical environmental factors of housing settlements that affect the presence of residential pests are dirty environments caused by garbage and dirty drainage / ditches. Meanwhile, biotic environmental factors in residential housing that affect the presence of pests are plants grown in residential areas in the form of ornamental plants and unkempt shade plants. The dirty condition of the residential environment is due to the lack of environmental cleaning activities and the not yet routine transportation of waste from residential homes to landfills. In addition, there is less care for ornamental plants and shade in the yard, such as pruning.